Pemanfaatan Media Sosial Untuk Berjualan Bakso Secara Online - Dona, Hesti Pestiko; Irwanto, Tito; Susena, Karona Cahya; Hidayah, Nenden Restu; Wijaya, Ermy (Universitas Dehasen Bengkulu, 2024)
This service activity was carried out in Air Kelinsar village, Ulu Musi District, Empat Lawang Regency, South Sumatra. This activity aims to utilize social media for home meatball sellers in Air Kelinsar village. Previously, meatball sellers in Air Kelinsar village only sold or traded meatballs at home and waited for buyers to come. The aim of this service is so that traders can get more buyers. Traders can use the Cash on Delivery system, which is a form of financial transaction where payment is made after the goods are delivered and received by the consumer. With this system, meatball traders can post photos of their sales on Facebook and people in Air Kelinsar village can order via inbox or contact Meatball Sellers. then the meatball seller can deliver the order according to the orderer's address, so that people in Air Kelinsar village who don't have vehicles or whose homes are far from where the seller is can order the meatballs.